Soil management is key to maintaining soil moisture in urban gardens facing changing climatic conditions. Issue 1 (December 2018) - Lin, Brenda; Egerer, Monika H.; Liere, Heidi; Jha, Shalene; Philpott, Stacy
Abstract Urban gardens are vital green spaces, providing food for residents and space for engaged citizenry and community development. In California, climate change conditions (heat and drought) are becoming more extreme, threatening the resilience of urban gardens. Water use restrictions limit the timing and amount of water that gardeners can access, exacerbating these climate challenges for urban food production. Together with volunteer gardeners, we examined how ambient temperature, water use, vegetation, ground cover, and soil management affect rates of soil moisture gain and loss in urban gardens for a six-week period in the summer of 2017, during the hottest part of the growing season. We found that plot-level management of soils is essential for creating urban garden plots that maintain stable levels of water within garden soils. Although plots with better soil quality (i.e. water holding capacity) experienced slower rates of soil moisture gain after a watering event, they also experienced slower rates of soil moisture loss after the event, leading to soils with more stable, less fluctuating moisture profiles over time. This may benefit gardeners because under extreme climates (such as heat and drought) and water use restrictions, maintaining more stable soils for their plants means that the soils will retain water over a longer period after each watering event. Overall, such results highlight that better soil management that improves soil quality measures such as water holding capacity are potential solutions for maintaining soil moisture and reducing water use under changing climate conditions.